2021
DOI: 10.1128/spectrum.00368-21
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Acanthamoeba castellanii Infected with Giant Viruses Quantitatively Revealed Process of Morphological and Behavioral Changes in Host Cells

Abstract: Quantitative analysis of the infection process is important for a better understanding of viral infection strategies and virus-host interactions. Here, an image analysis of the phase-contrast time-lapse movies displayed quantitative differences in the process of cytopathic effects due to the four giant viruses in Acanthamoeba castellanii , which were previously unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…The newly born virions were then released from host cells. Time-lapse phase-contrast light microscopy showed that the host amoeba cells exhibited intracellular bridge formation and rotational movement due to infection with the medusavirus, eventually causing the cells contract with death ( 14 ). This observation suggests that the nuclear function of amoeba cells is dominated by the replication of medusavirus and that progeny viruses cross the host cell membrane and are released at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…The newly born virions were then released from host cells. Time-lapse phase-contrast light microscopy showed that the host amoeba cells exhibited intracellular bridge formation and rotational movement due to infection with the medusavirus, eventually causing the cells contract with death ( 14 ). This observation suggests that the nuclear function of amoeba cells is dominated by the replication of medusavirus and that progeny viruses cross the host cell membrane and are released at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Each cell may develop different CPEs depending on which virus is currently replicating. For most infections involving amoebae and giant viruses, the standard observed CPE involves progressive cell rounding and loss of the trophozoite motility and lysis with subsequent release of the viral progeny from inside the cell (106). Amoebal viruses found in the above-described CPEs are mimiviruses, marseilleviruses, pandoraviruses, cedratviruses, faustoviruses, yasminevirus, and yaravirus (19,34,49,60,62,91,106,107).…”
Section: Virus-amoeba Interactionmentioning
confidence: 99%
“…For most infections involving amoebae and giant viruses, the standard observed CPE involves progressive cell rounding and loss of the trophozoite motility and lysis with subsequent release of the viral progeny from inside the cell (106). Amoebal viruses found in the above-described CPEs are mimiviruses, marseilleviruses, pandoraviruses, cedratviruses, faustoviruses, yasminevirus, and yaravirus (19,34,49,60,62,91,106,107). Different sets of CPEs may be observed in a different context of infection by other groups of amoebal viruses (Figure 5).…”
Section: Virus-amoeba Interactionmentioning
confidence: 99%
“… Acanthamoeba castellanii and related amoeba are considered to be the natural hosts of medusaviruses ( 1 ). The cytopathic effect (CPE) of the medusavirus causes rounding in infected A. castellanii cells at approximately 24 h postinfection (hpi) ( 5 ), even causing cyst formation in some cases ( 1 ). It has also been reported that this infection causes frequent rotational behavior and the formation of intercellular bridges in host cells ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cytopathic effect (CPE) of the medusavirus causes rounding in infected A. castellanii cells at approximately 24 h postinfection (hpi) ( 5 ), even causing cyst formation in some cases ( 1 ). It has also been reported that this infection causes frequent rotational behavior and the formation of intercellular bridges in host cells ( 5 ). In A. castellanii and Acanthamoeba rhysodes , cells with abnormal nuclei, such as multinucleated cells, frequently form intercellular bridges ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%